SIZE STRUCTURE IN SETTLEMENTS OF MUSSEL CRENOMYTILUS GRAYANUS AT THE COAST OF PRIMORSKY KRAI (JAPAN SEA) - L. G. Sedova; D. A. Sokolenko (Известия ТИНРО, 2019)
Current size structure of mussel Crenomytilus grayanus in the coastal waters at Primorye (Japan Sea) is considered on results of diving surveys conducted in 2003–2018. In total, 3635 mussel specimens were weighed and measured. Size structure of the mussel settlements is determined for each surveyed area using the data on shell length. The following parameters are evaluated: i) index of settling — ratio of mollusks number with shell < 30 mm (spat, yearlings) and > 50 mm (adults); ii) index of maturation — ratio of mollusks number with shell 35–50 mm (pre-reproductive) and > 50 mm (adult); iii) index of commercial recruitment — ratio of mollusks number with shell 90–100 mm (recruits) and >100 mm (commercial stock). The portion of mussels with non-commercial size exceeds 50 % in most settlements that indicates their active natural reproduction. The index of settling varied from 0.03 to 1.80, by areas; the index of maturation — from 0.04 to 0.58; the index of commercial recruitment — from 0.03 to 0.53.The indices variations are not proportional and depend on presence of the pelagic larvae in plankton and on survival of the juveniles. Low settling of spat in some years could be leveled by its good survival in favorable environments. Potential annual recruitment to commercial stock of C. grayanus in the coastal waters of Primorye is estimated as 5 . 103 t. State of the C. grayanus settlements beyond the areas of anthropogenic impact and active fishing is evaluated as stable.